Dynamic transcriptomics unveils parallel transcriptional regulation in artemisinin and phenylpropanoid biosynthesis pathways under cold stress in Artemisia annua - Yunxiao He; Wenjing Zhang; Xianghua Zuo; Jiangnan Li; Ming Xing; Yujiao Zhang; Jian You; Wei Zhao; Xia Chen (Scientific Reports)
Abstract Cold stress, a major abiotic factor, positively modulates the synthesis of artemisinin in Artemisia annua and influences the biosynthesis of other secondary metabolites. To elucidate the changes in the synthesis of secondary metabolites under low-temperature conditions, we conducted dynamic transcriptomic and metabolite quantification analyses of A. annua leaves. The accumulation of total organic carbon (TOC) in leaves under cold stress provided ample precursors for secondary metabolite synthesis. Short-term exposure to low temperature induced a transient increase in jasmonic acid synthesis, which positively regulates the artemisinin biosynthetic pathway, contributing to artemisinin accumulation. Additionally, transcripts of genes encoding key enzymes and transcription factors in both the phenylpropanoid and artemisinin biosynthetic pathways, including PAL, C4H, ADS, and DBR2, exhibited similar expression patterns, suggesting a coordinated effect between these pathways. Prolonged exposure to low temperature sustained high levels of phenylpropanoid synthesis, leading to significant increases in lignin, flavonoids, and anthocyanin. Conversely, the final stage of the artemisinin biosynthetic pathway is inhibited under these conditions, resulting in elevated levels of dihydroartemisinic acid and artemisinic acid. Collectively, our study provides insights into the parallel transcriptional regulation of artemisinin and phenylpropanoid biosynthetic pathways in A. annua under cold stress.